2010
DOI: 10.1007/s11738-010-0564-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of β-amino-butyric acid on resistance of cucumber against root-knot nematode, Meloidogyne javanica

Abstract: In this study, the effects of b-amino-butyric acid (BABA) on root-knot nematode(Meloidogyne javanica) infection of cucumber and accumulation of total phenolic compounds, hydrogen peroxide and activity of some enzymes related to plant defense mechanisms, i.e., guaiacol peroxidase (GPOX), polyphenol oxidase (PPO), catalase (CAT) in cucumber roots infected with nematode were investigated. Results of this study show that treating the cucumber seedlings with the above elicitor significantly reduces the nematode inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 33 publications
3
24
1
Order By: Relevance
“…In this study, some defense related enzymes were activated by BABA, such as PAL, POX and POD, which were all involved in the response to SA attack. The similar phenomenon was also reported in artichoke, cucumber, apple, grapefruit [12], [16], [70], [71]. Therefore, we believe that this is a common phenomenon in BABA-treated plants.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, some defense related enzymes were activated by BABA, such as PAL, POX and POD, which were all involved in the response to SA attack. The similar phenomenon was also reported in artichoke, cucumber, apple, grapefruit [12], [16], [70], [71]. Therefore, we believe that this is a common phenomenon in BABA-treated plants.…”
Section: Discussionsupporting
confidence: 87%
“…tomato in Arabidopsis thaliana L. [15], Meloidogyne javanica in Cucumis sativus L. [16], Myzus persicae in Sinapsis alba L. [17], and Acyrthosiphon pisum in Vicia faba L. var. minor [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, BABA was tested against M. incognita on tomatoes. Our findings were in agreement with previous studies (Sahebani et al 2011;Oka et al 1999).…”
supporting
confidence: 94%
“…BABA has also been used as a plant inducer against root-knot nematodes in tomatoes (Oka et al 1999). Sahebani et al (2011) investigated the effects of BABA on cucumbers infected with M. javanica and the accumulation of total phenolic compounds, hydrogen peroxide and the activity of some enzymes related to plant defence mechanisms. They showed that treating the cucumber seedlings with BABA significantly reduced the nematode galls, number of egg masses per plant and number of eggs per individual egg mass compared to the control.…”
mentioning
confidence: 99%
“…Induced systemic resistance to plant pathogen provides an ideal control measures against plant pathogens [3]. Chemical, physical and biological inducers to control the root knot nematodes were used [4]. In recent years, various chemical, physical and biological agents were used to induce resistance to many plant pathogens.…”
Section: Introductionmentioning
confidence: 99%